Soil fertility, nutrition and early growth of physic nut as affected by nitrogen fertilization - Freiberger, Mariângela Brito [UNESP]; Castoldi, Gustavo [UNESP]; Favare, Lilian Guimarães de [UNESP]; Guerrini, Irae Amaral [UNESP] (Taylor & Francis, 2014)
The initial growth and mineral nutrition of the physic nut (Jatropha curcas L.) as a function of nitrogen (N) fertilization was investigated. The transplanting of seedlings was carried out in plastic pots filled with 50 dm3 of a Rhodic Hapludox, under a plastic greenhouse. In addition to a control treatment, the dosages of 0, 40, 80, 120, and 160 mg dm−3 N were tested. The results demonstrated that N fertilization for the cultivation of physic nut could be added as top dressing from 60 days after planting with a dosage of 65 mg dm−3. A SPAD index of 46 can be used as a nutritional reference to its initial development. Furthermore, the results suggested that the order of nutrient accumulation by the physic nut plants is as follows: potassium (K) > N > magnesium (Mg) > calcium (Ca) > phosphorus (P) > sulfur (S) > iron (Fe) > manganese (Mn) > boron (B) > zinc (Zn) > copper (Cu).
Keywords: Jatropha curcas L.; SPAD index; Nutrient accumulation; Dry matter